2017
DOI: 10.1159/000475605
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Fatty Acid Composition and Dietary Pattern with the Risk of Non-Alcoholic Fatty Liver Disease in Patients Who Underwent Cholecystectomy

Abstract: Background/Aims: The relationship between diet and non-alcoholic fatty liver disease (NAFLD) in patients with gallstone disease and in those who have a high risk for NAFLD has not been investigated. This study was conducted to investigate the association between the risk of NAFLD and dietary pattern in patients who underwent cholecystectomy. Additionally, we assessed the association between erythrocyte fatty acid composition, a marker for diet, and the risk of NAFLD. Methods: Patients (n = 139) underwent liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
(56 reference statements)
2
27
0
Order By: Relevance
“…In this regard, Hossein et al reported that the consumption of boiled potato can eliminate the risk of diabetes because of the remarkably high fiber content ( 31 ). As reported previously ( 32 , 33 ), excessive intake of fried foods and low intake of tuber were risk factors for NAFLD in this study. Therefore, the general consensus from the reported studies, as well as the present findings, is that dietary interventions can also reduce the risk of NAFLD or improve already present NAFLD.…”
Section: Discussionsupporting
confidence: 86%
“…In this regard, Hossein et al reported that the consumption of boiled potato can eliminate the risk of diabetes because of the remarkably high fiber content ( 31 ). As reported previously ( 32 , 33 ), excessive intake of fried foods and low intake of tuber were risk factors for NAFLD in this study. Therefore, the general consensus from the reported studies, as well as the present findings, is that dietary interventions can also reduce the risk of NAFLD or improve already present NAFLD.…”
Section: Discussionsupporting
confidence: 86%
“…Among them, forty-seven articles were excluded because seven were review articles, eight were about adolescents, twenty-four were without the relevant exposure/outcomes and eight did not conform to the relevant study design. Finally, twenty-four articles were identified and included in this systematic review and meta-analysis (12)(13)(14)(15)18,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) . The study selection process is described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of eight studies assessed the effect of red meat consumption on the likelihood of NAFLD, which include seven crosssectional studies (with 5141 cases) and one case-control study (with 2974 cases) (18,34,36,38,44,48,49,52) . Meta-analysis results from the seven homogeneous cross-sectional studies (I 2 = 48•7 %, P = 0•069) showed a positive association between red meat consumption and the likelihood of NAFLD (OR = 1•121; 95 % CI 1•042, 1•207; P = 0•002) ( Fig.…”
Section: Red Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] To address this problem, dietary pattern analysis has emerged as an alternative and complementary approach to reporting the association of diet with the risk of chronic diseases, and it encompasses complex relations and synergistic effects of nutrients and foods consider the complexity of overall diet and facilitate nutritional recommendations. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%